Pengaruh Jumlah Sudu Prototype Pembangkit Listrik Tenaga Mikrohidro Tipe Whirlpool Terhadap Kinerja - Umurani, K; Siregar, Ahmad Marabdi; Al-Amin, Surya (Rekayasa Material, Manufaktur dan Energi, 2020)
The water turbine is a device that converts water flow energy into shaft mechanical energy. Before being converted into mechanical energy in the turbine, the potential energy needs to be converted into kinetic energy first. The vortex will move the turbine blades which cause the runner to rotate so that there is a change in the kinetic energy of the water into mechanical energy in the turbine which is used to drive the generator and then into electrical energy. The purpose of this research is to analyze the torque that occurs on the shaft and turbine power. Water is flowed to the test with a pump through a control valve. The water flow is read by a rotameter attached to the pipe to the upper reservoir, while the torque is measured using a load cell, while the rotation is measured using a photo sensor interrupt to read the movement of the counter wheel. Data from load cell and photo sensor interruptor is read using Arduino Uno then the data is stored on laptop in excel file using plx-daq software. The minimum torque for the 8 blades is 9,12 kg.mm and 7.61 kg.mm for 6 blades at a water flow rate of 90 l / min. The maximum torque occurs at the 8 blades of 10.06 kg.mm while the maximum torque at blade 6 is 9,12 kg.mm at the same water flow rate of 150 l / min. The minimum turbine power for the 8 blades is 0.47 W and 0.27 W for the 6 blades at a water flow rate of 90 l / min. The maximum turbine power at blade 8 is 1.03 W, while the maximum power at blade 6 is 0.91 W at the same water flow rate of 150 l / min. From the data analysis, it can be seen that the power for the turbine with the number of blades 8 tends to be greater than the power for the turbine with 6 blades, but if the percentage increases in power between the 8 blades and 6 blades the trend decreases even though the flow rate is increasing.